EFFECT OF EXTRA VIRGIN OLIVE OIL ON POSTPRANDIAL BLOOD GLUCOSE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Galang, Daphne Gayle; Isidro, Maria Jocelyn; Gonzales, Ma. Cecilia; Macabuag-Oliva, Andrea (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The burden of diabetes continues to rise despite the emergence of new medications. Hence, all possible treatment modalities including the use of our readily available herbs and oils are explored. Extra virgin olive oil (EVOO) is known for its cardiovascular effects and its effect on glucose lowering. However, there has been no study on the efficacy of extra virgin olive oil on glucose lowering among Filipino patients with Type 2 Diabetes Mellitus. The primary objective of this study is to determine whether a significant difference exists in the 2-hour postprandial blood glucose of meals containing EVOO and meals without EVOO in patients with Type 2 Diabetes Mellitus. METHODOLOGY Thirteen patients were included in this randomized controlled cross-over trial. They received a test meal with EVOO or no EVOO followed by a one week wash out period, in which the subjects were given the other intervention. The primary outcome is the trans-meal blood glucose, which is calculated as the percent change in 2-hour postprandial blood glucose. RESULTS In group A, there was a noted 88.55% increase in 2-hour post prandial blood glucose in taking meals with EVOO, compared to 72.11% change in meals without EVOO. The same was observed in Group B, where there was a 71.08% and 49.22% increase in 2-hour postprandial blood glucose in meals with EVOO and without EVOO, respectively. The difference was significant with a p-value of 0.044. Free fatty acids inhibit glucose transport and insulin secretion, this effect may be more predominant in Asian type 2 Diabetes Mellitus patients. CONCLUSION This study found that adding extra virgin olive oil on top of meals provided no additional benefit in terms of post-prandial glucose excursion.